2021
DOI: 10.1039/d1sc00703c
|View full text |Cite
|
Sign up to set email alerts
|

The key role of the latent N–H group in Milstein's catalyst for ester hydrogenation

Abstract: We report a detailed mechanistic study of ester hydrogenation catalyzed by the activated form of Milstein’s catalyst. Catalyst activation leads to the replacement of a dialkylamino side group with an NHEt group, which has a key role in catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 98 publications
3
24
0
Order By: Relevance
“…Several ruthenium and manganese pincer complexes were screened for the amide synthesis under Et 2 O reflux (boiling point 34.6 °C) in the presence of catalytic amounts of t -BuOK. Interestingly, among these complexes, Ru–PNNH complexes 1 and 2 , featuring a terminal N–H moiety, displayed catalytic activities toward amide formation even at this low temperature (entries 1–2). Ru–PNNH complexes 1–3 are capable of two distinct modes of metal–ligand cooperation (MLC), amido–amine and aromatization–dearomatization, unlike complexes 4–6 , where only aromatization–dearomatization is possible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several ruthenium and manganese pincer complexes were screened for the amide synthesis under Et 2 O reflux (boiling point 34.6 °C) in the presence of catalytic amounts of t -BuOK. Interestingly, among these complexes, Ru–PNNH complexes 1 and 2 , featuring a terminal N–H moiety, displayed catalytic activities toward amide formation even at this low temperature (entries 1–2). Ru–PNNH complexes 1–3 are capable of two distinct modes of metal–ligand cooperation (MLC), amido–amine and aromatization–dearomatization, unlike complexes 4–6 , where only aromatization–dearomatization is possible.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, among these complexes, Ru–PNNH complexes 1 and 2 , featuring a terminal N–H moiety, displayed catalytic activities toward amide formation even at this low temperature (entries 1–2). Ru–PNNH complexes 1–3 are capable of two distinct modes of metal–ligand cooperation (MLC), amido–amine and aromatization–dearomatization, unlike complexes 4–6 , where only aromatization–dearomatization is possible. Ru–P Ph NNH complex 3 , with electron-withdrawing Ph substituents on the P donor atom, did not show catalytic activity at this temperature (entry 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Recent work on PNN systems bearing an NEt 2 side-arm donor has suggested that dehydroalkylation of the CH 2 NEt 2 arm can occur during catalytic ester hydrogenation to form a secondary amine donor NHEt. 43 The secondary amine PNN ligand is thought to favour a traditional Lewis base assisted MLC mechanism via protonation-deprotonation of the NHEt moiety, rather than an aromatisation-dearomatisation mechanism. 43 The fact that mechanisms through which prominent catalysts operate are the subject of ongoing debate decades after their discoveries highlights the difficulty in establishing the role of cooperative processes in catalysis.…”
Section: Aromatisation-dearomatisationmentioning
confidence: 99%
“…Heating the complex at 40 °C for two weeks does however lead to the establishment of the same cis/trans equilibrium, without any deuteration of the complex hydrides, or of the dissolved H 2 signal, allowing us to establish a ratio of ~10 : 1.2 for the trans:cis 9 b : 9 a H 2 complex equilibrium (Supporting Information, pp. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Reactivity Of 4meà Pnp Complexes With Hydrogen Gasmentioning
confidence: 99%